Brillouin Spectroscopy of Gelatin Gel and the Use of a CD Area Detector - Zhao, Peizhen (My University, 1995)
Brillouin scattering method was used to study two kinds of materials: gelatin gel and quasicrystal Al₆₃.₅Cu₂₄.₅Fe₁₂. The measurements of Brillouin shift and width for gelatin-water system were carried out as a function of temperature, concentration, time and thermal history. New results and a phase diagram for melting were obtained. The results are discussed using different models. The longitudinal storage modulus of the gel network, the frictional damping parameter and the melting enthalpy have been evaluated. However, in order to explain all the experimental results and get the more accurate values for those parameters, a more perfect theory for this biopolymer system is needed. A more efficient technique -- CCD used as a detector, is described, too.
Keywords: Physics; Physics